Answer:
K=J+6/2
Step-by-step explanation:
J= -2(3-k)
simplify whats in the bracket
J= -6+2k
J+6=2k
Divide both sides by 2
J+6/2=2k/2
2 and 2 will cancel out
remaining K
So, Therefore K=J+6/2
Hope it Helped
Answer:
x = 9.6
Step-by-step explanation:
Before we can figure out what x is, we need to figure out what the unlabeled side is. To figure that out, multiply the hypotenuse (12) by the sine of the angle labeled (34)
12 * sin(34)
<em>sin(34) equals 0.559192903470747; I'll round it to 0.6 for convenience.</em>
12 * 0.6
<em>Now simply multiply 12 by 0.6 to get 7.2.</em>
The unlabeled side is approx. 7.2 units long.
Now we know what the unlabeled side is. Now, to find x, find the square root of 12 squared minus 7.2 squared.
x = √12² - 7.2²
<em>12 squared is 144; 7.2 squared is 51.84.</em>
x = √144 - 51.84
<em>Subtract 51.84 from 144 to get 92.16.</em>
x = √92.16
<em>The square root of 92.16 is 9.6 (on the spot!).</em>
x equals 9.6.
So you would start with the square and do 18 times 18 which equals 324 then for the triangle it's base times height divided by two so 9 times 18 divided by 2 which equals 81 then you add the triangle plus the square and your final answer is
answer:405
Answer:
108° Make me Brainliest pls
Answer:
9
Step-by-step explanation:
3,000/ 270 = 11.11
100/ 11.11 = 9